Gender Differences in Cardiovascular Risk and Clinical Characteristics Among Psoriatic Arthritis Patients - Ping Seung Ong; Mat Hasnah; Lay Kim Tan; Sulaiman Wahinuddin (Journal of Clinical Rheumatology and Immunology)
Background Psoriatic arthritis (PsA) is characterized by a higher prevalence of metabolic syndrome and is associated with chronic inflammation, which increases the likelihood of developing cardiovascular disease. The aim of our study was to assess the differences of cardiovascular risk and clinical characteristics among psoriatic arthritis between the gender. Methods In this cross-sectional study, PsA patients who attended a single rheumatology referral center without cardiovascular disease (CVD) were recruited. CVD was defined as the occurrence of coronary artery disease or cerebrovascular ischemic disease events. This study utilized the atherosclerotic cardiovascular disease (ASCVD) score to predict the 10-year risk of atherosclerotic cardiovascular events, analyzing any differences or similarities in risk between male and female patients. Results We enrolled a total of 246 patients, comprising 108 males and 138 females. The mean age of the participants was 57 years (± 13.8) for males and 55 years (± 13.3) for females. Female patients exhibited significantly higher erythrocyte sedimentation rates and were more likely to be using two or more conventional synthetic disease-modifying antirheumatic drugs. Additionally, a significantly higher proportion of females had scalp involvement in their psoriasis compared to males (p [Formula: see text] 0.05). Male patients with PsA had a lower ASCVD score (B=-1.008, 95% CI: -1.489, -0.526) compared to female PsA patients. However, there was no statistically significant association between gender and multiple domains of PsA. Conclusion The higher ASCVD scores in female PsA patients underscore the need for proactive cardiovascular risk management, including lifestyle interventions and pharmacological treatments, to mitigate the risk of future cardiovascular events. Further research is required to explore the underlying mechanisms driving these gender differences and to develop tailored strategies for the prevention and management of comorbidities in PsA patients.